The Effect Of Service Quality, Location, And Satisfaction On Bpjs Patient Loyalty at The Harmonisasi Chi Primary Clinicmedika In Bengkulu City - Marice Anggeria; Yudi Irawan Abi; Ermy Wijaya (Jurnal Ekonomi Islam, Akuntansi, dan Manajemen, 2026)
This study aims to determine the effect of Service Quality, Location, and Satisfaction on BPJS Patient Loyalty at the Pratama Harmonisasi Chi Medika Clinic in Bengkulu City. The type of research used is quantitative with an associative approach, where data were obtained through distributing questionnaires to 110 BPJS patient respondents. The results of multiple linear regression analysis produced the equation Y = 3.372 + 0.260X₁ + 0.155X₂ + 0.508X₃ + e. The F test shows that Service Quality, Location, and Satisfaction simultaneously have a significant effect on Patient Loyalty with an Fcount value of 1109.856 and a significance of 0.000 <0.05. The coefficient of determination (R²) value of 0.969 indicates that 96.9% of the variation in Patient Loyalty is explained by these three variables, while 3.1% is influenced by other factors outside the study. The partial t-test results show that Service Quality (t = 7.599), Location (t = 4.273), and Satisfaction (t = 18.295) have a positive and significant effect on Patient Loyalty, where Satisfaction is the most dominant variable.